Analysis of Sustainability Status, Land Availability and Projected Land Needs for the Development of Residential Areas in South Cikarang District - Nur Handayani; Janthy T. Hidayat; Mujio Mujio (Publikasi Indonesia, 2024)
National economic growth is greatly influenced by industrial growth. Industrial activities in South Cikarang sub-district generally have an impact on regional development and increasing community welfare, industrial development can also increase population. This increase occurred due to the need for a labor in numbers that could not all be provided by the labor in industrial locations, resulting in population migration. The increase in population brings major changes to the increase in basic human needs, namely the need for land as a place to live which will continue to increase naturally, while land is limited and tends to experience environmental degradation. The existence of industry and the increase in population threaten the sustainability of residential areas. The aim of this research is to identify the condition of existing settlements; sustainability status in ecological, economic, social and institutional dimensions; analyzed the availability of residential land and the need for residential land in 2031. The analysis techniques used were spatial analysis, Multi Dimensional Scaling (MDS) analysis, descriptive analysis. The results of the research show that the research location has a fairly sustainable and sustainable status in developing residential areas. In 2031, several villages in the research area lack land for residential areas, so direction is needed regarding plans for sustainable residential area development.